On The Effectiveness of Hierarchical Zeolite Catalyst for Isomerization of Biomass-Derived Compound - Juli azhari, Noerma; Mardiana, St; Kadja, Grandprix Thomryes Marth (Journal of Research and Development on Nanotechnology, 2021)
The expansion of catalytic technologies in biomass conversion has received increasing attention due to their promising in the sustainable economy. As the solid acid catalyst, zeolite becomes an excellent catalyst for the isomerization reaction of biomass conversion. Nevertheless, the diffusion limitation results from the micropore channel in zeolite rendering the development of zeolite with the additional pores, known as hierarchical zeolite. Up to now, hierarchical zeolites attract much attention appertain with their outstanding properties in the isomerization reaction. Accordingly, many efforts to fabricate hierarchical zeolites, such as top-down and bottom-up methods, have been conducted and grown over the decades. This review examines the current strategies in designing hierarchical zeolite for biomass isomerization. We mainly dwell on the isomerization process of biomass from cellulosic and fatty acids. This review also provides the future challenges and opportunities of the hierarchical zeolite for further improvement in biomass isomerization research.